Rekonstruksi Teori Hukum dalam Masyarakat Modern - A. Hans Tayeb Adrian; Mira Nila Kusuma Dewi; Nur Wahyu Hidayat; Khidir (Al-Istinbath : Jurnal Ilmu Hukum dan Hukum Keluarga Islam, 2025)
The reconstruction of legal theory in modern society has become a crucial agenda to address the challenges of rapid social change, the penetration of digital technology, and the increasingly complex relations between the state, society, and individuals. Law can no longer be maintained as a static normative instrument, but must be understood as a dynamic system that both shapes and is shaped by social reality. This reconstruction emphasizes the need for a paradigm shift that shifts the orientation of law from a mere set of rules to a transformative force capable of delivering substantive justice. In the context of modernity, law is required to be more sensitive to the diversity of values, societal needs, and universal principles of human rights. The reconstruction process includes strengthening philosophical foundations that place human dignity at the center of orientation, developing an interdisciplinary approach that integrates sociological, ethical, political, and technological perspectives, and restructuring law enforcement methods to be more transparent, accountable, and adaptive to changing times. Through this reconstruction, law not only functions to regulate but also plays a role in protecting society from abuse of power, ensuring certainty in social interactions, and encouraging the creation of a more just and humane life. Law becomes an instrument that balances individual and collective interests, strengthens social cohesion, and accommodates cultural and value plurality. Thus, the reconstruction of legal theory is not merely an academic project, but also a civilizational strategy for building a legal system that is inclusive, progressive, and relevant to the dynamics of modern society. This effort is expected to produce a legal order that is responsive, visionary, and capable of serving as the foundation for a just civilization. Abstrak Rekonstruksi teori hukum dalam masyarakat modern menjadi agenda penting untuk menjawab tantangan perubahan sosial yang cepat, penetrasi teknologi digital, serta semakin kompleksnya relasi antara negara, masyarakat, dan individu. Hukum tidak lagi dapat dipertahankan sebagai perangkat normatif yang statis, melainkan harus dipahami sebagai sistem dinamis yang membentuk sekaligus dibentuk oleh realitas sosial. Rekonstruksi ini menekankan perlunya pembaruan paradigma yang menggeser orientasi hukum dari sekadar seperangkat aturan menuju kekuatan transformatif yang mampu menghadirkan keadilan substantif. Dalam konteks modernitas, hukum dituntut untuk lebih sensitif terhadap keragaman nilai, kebutuhan masyarakat, dan prinsip-prinsip universal tentang hak asasi manusia. Proses rekonstruksi mencakup penguatan fondasi filosofis yang menempatkan martabat manusia sebagai pusat orientasi, pengembangan pendekatan interdisipliner yang mengintegrasikan perspektif sosiologi, etika, politik, dan teknologi, serta penataan kembali metode penegakan hukum agar lebih transparan, akuntabel, dan adaptif terhadap perkembangan zaman.Melalui rekonstruksi ini, hukum tidak hanya berfungsi mengatur, tetapi juga berperan melindungi masyarakat dari penyalahgunaan kekuasaan, memastikan kepastian dalam interaksi sosial, serta mendorong terciptanya kehidupan yang lebih adil dan manusiawi. Hukum menjadi instrumen yang menyeimbangkan kepentingan individual dan kolektif, memperkuat kohesi sosial, serta mengakomodasi pluralitas budaya dan nilai. Dengan demikian, rekonstruksi teori hukum tidak sekadar merupakan proyek akademik, tetapi juga strategi peradaban untuk membangun sistem hukum yang inklusif, progresif, dan relevan dengan dinamika masyarakat modern. Upaya ini diharapkan mampu melahirkan tatanan hukum yang responsif, visioner, dan mampu menjadi fondasi bagi peradaban yang berkeadilan